Tinjauan Terhadap Sinkronisasi Perencanaan Pembangunan Pasca Pemilihan Kepala Daerah Serentak di Kota Cimahi Tahun 2017 - Kurniansyah, Dadan (Jurnal Politikom Indonesiana, 2018)
Cimahi City is one of the three regions that carried out national concurrent election in West Java Province. The victory of the pair Ir. H. Ajay M. Priatna, MM and Lieutenant Colonel (Ret.) Ngatiyana as determined by KPU on February 23, 2017 must undergo a long journey towards the inauguration for 9 (nine) months plus 6 (six) months of the Regional Medium Term Development Plan (RPJMD) for 2017-2022. Thus, the government for the 2017-2022 period only has 4 (four) years effective time to carry out its vision and mission. This study will review the synchronization of development planning after simultaneous regional head elections in Cimahi City in 2017, with descriptive methods through a qualitative approach. The source of research data is a group of government officials involved in the synchronization process. The study concluded that the synchronization of development planning in Cimahi City was in accordance with the legislation governing regional planning, the synchronization process of development planning was in transition to leadership which affected the drafting of the RKPD 2018 which became the basis for the RAPBD KUA-PPAS 2018 document. Although there are still human resource capacity constraints and an understanding of the technical division employee and the budget burden for 2018, the synchronization pattern of program priorities becomes a strategy to achieve leadership effectiveness Mayor/Vice Mayor of Cimahi Period 2017-2022. Keywords: synchronization, leadership transition and development planning